Site‐specific distribution of oak rhizosphere‐associated oomycetes revealed by cytochrome c oxidase subunit II metabarcoding. Issue 18 (16th August 2019) - Sapp, Melanie; Tyborski, Nicolas; Linstädter, Anja; López Sánchez, Aida; Mansfeldt, Tim; Waldhoff, Guido; Bareth, Georg; Bonkowski, Michael; Rose, Laura E.
Abstract: The phylum Oomycota comprises important tree pathogens like Phytophthora quercina, involved in central European oak decline, and Phytophthora cinnamomi shown to affect holm oaks among many other hosts. Despite the importance to study the distribution, dispersal and niche partitioning of this phylum, metabarcoding surveys, and studies considering environmental factors that could explain oomycete community patterns are still rare. We investigated oomycetes in the rhizosphere of evergreen oaks in a Spanish oak woodland using metabarcoding based on Illumina sequencing of the taxonomic marker cytochrome c oxidase subunit II (cox2). We developed an approach amplifying a 333 bp long fragment using the forward primer Hud‐F ( Mycologia, 2000) and a reverse primer found using DegePrime ( Applied and Environmental Microbiology, 2014). Factors reflecting topo‐edaphic conditions and tree health were linked to oomycete community patterns. The majority of detected OTUs belonged to the Peronosporales. Most taxa were relatives of the Pythiaceae, but relatives of the Peronosporaceae and members of the Saprolegniales were also found. The most abundant OTUs were related to Globisporangium irregulare and P. cinnamomi, both displaying strong site‐specific patterns. Oomycete communities were strongly correlated with the environmental factors: altitude, crown foliation, slope and soil skeleton and soil nitrogen. Our findings illustrate the significance of small scale variation in habitat conditions for the distribution of oomycetes and highlight the importance to study oomycete communities in relation to such ecological patterns. Abstract : The phylum Oomycota comprises important tree pathogens, but knowledge on environmental factors that could explain their community patterns is scarce. To advance our understanding, oomycetes in the oak rhizosphere were studied using metabarcoding of the taxonomic marker cytochrome c oxidase subunit II and linked to biotic and abiotic variables. Oomycete communities were strongly correlated with the environmental factors altitude, crown foliation, slope and soil skeleton and soil nitrogen.